A Method for the Determination of Relative Crystallinity of Minerals by X-Ray Diffraction (Biological Sciences - PJSIR, 2006)
. X-ray diffraction spectra of smithsonite, fluorite, zircon, gibbsite, quartz, aragonite, albite, calcite, dolomite, anatase, barite, wollastonite and siderite have been recorded. The relative percentage crystallinity of these were calculated with the help of two programmes, namely, PowderX and WinPlotr. These two programmes have simplified the calculation of relative percentage crystallinity of various materials. Most of the X-ray spectra were very good and without noise. The noise of the spectra, when present, was removed with the programme PowderX and the spectrum was also levelled before the calculation of percentage crystallinity. The spectra of highly crystalline materials showed sharp high intensity peaks with small base. The degree of crystallinity has been determined by WinPlotr using integration method and by PowderX programme using area of the triangle method. Both of these programmes showed similar results, with the exception of a few spectra where the specimens were paracrystalline and amorphous.